Public health spending, governance and child health outcomes: revisiting the links - Hu, Bingjie (Archīum Ateneo, 2013)
This paper empirically examines the determinants of child health in developing countries and how public policy may interact with these determinants. It improves on previous empirical studies by conducting a more careful analysis of the determinants controlling for possible endogeneity, and by using a more comprehensive and richer panel dataset, drawing on a health database covering 136 countries over 1960–2005, supplemented by the latest World Development Indicators dataset as well as data on a broad variety of alternative indicators of governance, such as those from the International Country Risk Guide and the Open Budget Index. We find that both public spending on healthcare and the quality of governance matter for the reduction of child mortality rates. However, our mixed results on the interaction of governance with public spending throw some doubt on the conclusiveness of previous empirical studies.